2019
DOI: 10.1038/s41385-018-0127-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated antigen-presenting cell alterations promote dry-eye inducing Th1 cells

Abstract: Aging is a significant risk factor for dry eye. Here we used a murine aged mode to investigate the effects of aging on antigen presenting cells (APCs) and generation of pathogenic T helper (Th)1. Our results showed that APCs from aged mice accumulate at the conjunctiva, have higher levels of co-activation marker CD86 and lower aldehyde dehydrogenase activity. Using topical ovalbumin peptide as a surrogate antigen, we observed an increased number of antigen-loaded APCs in the draining cervical lymph nodes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 63 publications
2
31
0
Order By: Relevance
“…Given that the survival of immune cells may be affected differentially by the surrounding environment where the resident tissue cells provide survival factors, the shifting of IL-17 + cell or IFN γ + cell changes from 1 year of age to 2 years of age is presumably affected by the (1) pathogenic increase of autoimmunity, (2) age-dependent cellular senescence, or (3) different survival rates based on where they reside. The changes in effector T cells were accompanied by increased populations of activated antigen-presenting cells in the DLNs, suggesting that an increased presence of the antigen is crucial to age-related dry eye, as previously reported [4]. High levels of IFN-γ in the conjunctiva are known to impact the loss of goblet cells [5,12].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Given that the survival of immune cells may be affected differentially by the surrounding environment where the resident tissue cells provide survival factors, the shifting of IL-17 + cell or IFN γ + cell changes from 1 year of age to 2 years of age is presumably affected by the (1) pathogenic increase of autoimmunity, (2) age-dependent cellular senescence, or (3) different survival rates based on where they reside. The changes in effector T cells were accompanied by increased populations of activated antigen-presenting cells in the DLNs, suggesting that an increased presence of the antigen is crucial to age-related dry eye, as previously reported [4]. High levels of IFN-γ in the conjunctiva are known to impact the loss of goblet cells [5,12].…”
Section: Discussionsupporting
confidence: 73%
“…This finding may present different age-related changes of IL-17 + or IFNγ + cells, depending on the location. A previous report also showed that the percentage of IFNγ + cells increased across all tissues (conjunctiva, LG, and lymph nodes) at 24 months, while, on the contrary, the percentage of IL-17 + cells decreased in the LG and conjunctiva, unlike in the lymph nodes, at 24 months [4]. A healthy human study has demonstrated that age deeply impacts the contraction of CD4 + IL-17 + cell populations in peripheral blood, while the population of CD4 + IFNγ + cells are relatively maintained, regardless of age [13].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…To avoid excessive inflammation and tissue damage, immune tolerance mechanisms are crucial. Goblet cell-associated passage of antigens through the conjunctiva and controlled processing plays a crucial role in the induction of the local immune tolerance, but is disturbed in dry eye disease and age-related ocular surface inflammation [ 33 , 34 ]. Previously we demonstrated that particles and bacteria are also directly transported into CALT [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has become evident that both innate and adaptive immunity immune responses are involved [ 51 ]. Animal models have shown active participation of CD4+ T cells [ 52 , 53 ]. Although both sexes are affected, dry eye affects more women than men, and its prevalence increases sharply in women in the 5th decade [ 10 , 11 , 13 , 54 , 55 , 56 ] Because of its strong association in women and perimenopause, the influences of sex hormones have been postulated as playing roles in either promoting or ameliorating dry eye disease [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%